Modernization and new services of the Brazilian active control network - Fortes, L. P S; Costa, S. M A; Abreu, M. A.; Silva, A. L.; Júnior, N. J M; Barbosa, K.; Gomes, E.; Monico, J. G. [UNESP]; Santos, M. C.; Tétreault, P. (Springer Nature, 2012)
The Brazilian Network for Continuous Monitoring of GNSS - RBMC is a national network of continuously operating reference GNSS stations. Since its establishment in December of 1996, it has been playing an essential role for the maintenance and user access of the fundamental geodetic frame in the country. In order to provide better services for RBMC, the Brazilian Institute of Geography and Statistics - IBGE and the National Institute of Colonization and Land Reform - INCRA are both partners involved in the National Geospatial Framework Project - PIGN. This paper provides an overview of the recent modernization phases the RBMC network has undergone highlighting its future steps. These steps involve the installation of new equipment, provide real time data from a group of core stations and compute real-time DGPS corrections, based on CDGPS (The real-time Canada-Wide DGPS Service) (The Real-Time Canada-Wide DGPS Service. http://www.cdgps.com/ 2009a). In addition to this, a post-mission Precise Point Positioning (PPP) service has been established based on the current Geodetic Survey Division of NRCan (CSRS-PPP) service. This service is operational since April 2009 and is in large use in the country. All activities mentioned before are based on a cooperation signed at the end of 2004 with the University of New Brunswick, supported by the Canadian International Development Agency and the Brazilian Cooperation Agency. The Geodetic Survey Division of NRCan is also participating in this modernization effort under the same project. This infrastructure of 66 GNSS stations, the real time, post processing services and the potentiality of providing Wide Area DGPS corrections in the future show that the RBMC system is comparable to those available in USA and Europe. © Springer-Verlag Berlin Heidelberg 2012.